(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
This scientific study examines the impact of the global economic situation on the management of raw material reserves in the oil refining industry. In the context of fluctuating oil prices, changing consumer demand and geopolitical factors, effective inventory management is becoming a key element of companies’ strategic planning. However, the volatility of the regulatory environment creates difficulties in inventory management, requiring companies to be flexible in their operational processes and implement systems for tracking legislative initiatives. Thus, the implementation of the proposed measures will create the foundation for the development of the organization, ensuring stable functioning during periods of market turbulence and economic changes.